Analisis Profil Latent Terhadap Keterlibatan Mahasiswa dalam Pendidikan Kalkulus Terintegrasi STEM: Pengembangan Karakter dan Prestasi Akademik di Perguruan Tinggi Indonesia - Deby Erdriani; Zelhendri Zen; Fetri Yeni; Mahdalena Prihatin Ningsih; Ega Harna B; Firmawati; Helmiyanti (Jurnal Penelitian Pendidikan IPA, 2026)
This study employed Latent Profile Analysis (LPA) to investigate engagement patterns among Indonesian university students (N = 81) in a calculus course integrated with STEM through engineering case studies and digital tools. A cross-sectional design using a multidimensional engagement questionnaire identified three distinct profiles: Highly Engaged Digital Learners (22.20%), Minimally Engaged Learners (3.70%), and Moderately Engaged Learners Requiring Support (74.10%). ANOVA results revealed that Highly Engaged Digital Learners achieved significantly superior calculus performance (mean score = 89.70) compared to other profiles (mean difference = 17.30 points, p < 0.001). MANOVA further indicated that this group demonstrated substantially greater development of character virtues, including perseverance, intellectual honesty, and collaborative ethics (all p < 0.001). The findings confirm that STEM-integrated calculus education, when effectively engaging students, serves a dual pedagogical function, simultaneously advancing technical competencies and ethical reasoning. This highlights its transformative potential in fostering holistically developed professionals, aligning with Sustainable Development Goal 4 (Quality Education). Strategic educational responses should include early engagement profiling and targeted support to maximize these benefits.